Temporary intravascular shunts and limb salvage in civilian vascular trauma - Martinelli, Ombretta; Miceli, Francesca; Cuozzo, Simone; Irace, Francesco Giosuè; Avenia, Stefano; Iannone, Immacolata; Clementi, Ilaria; Sapienza, Paolo; Bellini, Maria Irene (Frontiers in Surgery, 2023)
Background Temporary intravascular shunts (TIVS) may allow quick revascularization and distal reperfusion, reducing the ischemic time (IT) when an arterial injury occurs. Furthermore, TIVS temporarily restore peripheral perfusion during the treatment of concomitant life-threatening injuries or when patients require evacuation to a higher level of care. Notwithstanding, there are still disputes regarding the use of TIVS, in view of the paucity of evidence in terms of potential benefits and with regard to the anticoagulation during the procedure. The present study aimed to assess TIVS impact, safety, and timing on limb salvage in complex civilian vascular traumas. Patients and methods Data were retrieved from the prospective database of our department, which included all patients hospitalized with a vascular injury of the extremities between January 2006 and December 2022. Patients undergoing TIVS during vascular injury management were included in group A, and those who could not postpone immediate care for TIVS insertion were included in group B (control group). Data concerning the times required for extremity revascularization or other surgical procedures such as orthopedic interventions and the time of limb ischemia were compared between the two groups. A comparison of the postoperative course between the two groups was also performed. Results A total of 53 patients were included: group A (TIVS insertion, n = 31) and group B (control, n = 22). Revascularization time significantly differed (p = 0.002) between the two groups, which is lower in group A (4.17 ± 2.37 h vs. 5.81 ± 1.26 h). TIVS positively affected the probability of limb salvage (p = 0.02). At multivariate analysis, the factors independently associated with limb salvage were TIVS usage, the necessity of hyperbaric oxygen therapy, and the total IT. In group A, there were three deaths and one major amputation, and in group B, there were two deaths and four major amputations. Conclusions The use of TIVS minimizes revascularization time and improves limb salvage probability. A multidisciplinary approach is recommended, and correct surgical timing is key to ensure the best outcome.